Investigation of mechanical and physical properties of bioplastic from Dioscorea hispida (Ubi Gadong) starch extracted by mechanical method - Ab Hadi, Nur Adillah (2020)
In this study, the bioplastic from Dioscorea hispida (ubi gadong) starch were investigated. It was due to the properties of petrochemical based bioplastic that has poor biodegradability rate, which giving harm to the environment. The starch from D.hispida tuber was extracted using the mechanical method which the yield was 40.31%. The bioplastic with different ratios of starch and glycerol, which were bioplastic 1, 2, 3,4 and 5 were investigated. The composition compound in the starch sample was studied by using Fourier transform infrared spectroscopy (FTIR) analysis. The mechanical properties such as tensile strength and elongation break were tested using a universal testing machine (UTM) same goes to the physical properties such moisture absorption and biodegradability were studied. Overall, the results show the bioplastic 1 with the lowest glycerol content had the highest tensile strength which was 17 MPa and elongation break was 9.87%. The moisture absorption and biodegradability rate increase when the glycerol content increased. All the bioplastic included 1,2,3,4 and 5 were fully degraded after six days.